ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Repair of craniofacial bone defects remains highly challenging due to the region's complex anatomy close to vital brain marrow tissue. How to make a safe and efficient repair without disturbing surrounding tissues is critical, especially in external-stimulus-enhanced regeneration strategy. Magnetic hyperthermia therapy (MHT), due to its ability of uniform heat generation and good penetration, has gained increasing attention in bone repair. An asymmetric magnetic microspheres hybrid hydrogel was developed with magnetothermal responsiveness for targeted heating at the defect, preventing the risk of potential thermal injury to adjacent critical tissues. Guided by an external magnetic field, magnetic microspheres distributed in the upper side of the hydrogel achieved localized mild heating (40°C-42°C) under an alternating magnetic field (AMF), whereas the lower side remained within a physiologically safe temperature (< 38°C). In vitro and in vivo experiments showed that the asymmetric magnetic hydrogel under safe magnetothermal stimulation significantly enhanced the osteogenic differentiation and vascularization. Furthermore, transcriptomic analysis and histological staining suggested that this platform may convert external magnetothermal stimulation into intracellular signals by activating the PI3K-Akt pathway and upregulating key osteogenic and angiogenic markers. Overall, this asymmetric magnetothermal hydrogel offers a spatially controlled, safe, and effective strategy for bone regeneration.